Evaluation of the in silico Toxicity of monoterpene Verbenone (Research, Society and Development, 2020)
The present work aims to evaluate the in silico toxicity of the monoterpene verbenone. The in silico toxicity assessment was performed using the free software AdmetSAR®, through which the following parameters were analyzed: AMES Mutagenic Potential, Acute Oral Toxicity (TOA), Carcinogenic Potential (PC) and Carcinogenicity (Car). Verbenone did not show mutagenic potential by the AMES test, as well as being non-carcinogenic or carcinogenic and on Acute Oral Toxicity, it was classified in category III, according to USEPA data, which means that the LD50 varies between 500-5000mg/kg. Therefore, it is concluded that the monoterpene verbenone is not mutagenic, carcinogenic or carcinogenic and presented a moderate acute oral toxicity index. That is, according to the in silico test, it is a viable substance for use in humans.